FATIGUE ANALYSIS OF HIGH SPEED RAILWAY STEEL BRIDGE WITH VARIOUS CODE STANDARDS - Rahman Tri Jaya, Faizal
Jakarta-Bandung High-speed Railway is the first High-speed Railway (HSR) in Southeast Asia. Currently there is no code that regulates HSR in Indonesia, the Standar Nasional Indonesia (SNI) is limited to highways and trains with normal speeds. Several general codes must be adopted for HSR, that’s are Chinacode, Eurocode, and the American Railway Engineering and Maintenance of Way Association (AREMA). In this research, fatigue analysis took the case study of the DIK1114 steel truss bridge. HSR traffic provides continuously varying stresses causing the bridge to fatigue. Components on the bridge that are potential for fatigue accur were identified based on analysis with the three codes. Fatigue assessment with Chinacode shows results that are close to actual conditions. Eurocode shows fatigue assessment results that are more conservative than Chinacode and are representative because they use the S-N Curve to calculate the number of cycles and predict the fatigue life from the accumulation of cycles each year. Meanwhile, AREMA shows the most conservative results, the resulting fatigue life value is shorter compared to other codes. Furthermore, periodic fatigue analysis is required by taking into account existing damage to the bridge structure such as cracks and corrosion. By this research hope will encourage regulators to create a code SNI that regulates HSR in Indonesia.